2019
DOI: 10.1021/acsami.9b17520
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Oxide Sulfate-Carbon (ZrOSO4@C) Derived from Carbonized UiO-66 for Selective Production of Dimethyl Ether

Abstract: Methanol dehydration process to dimethyl ether (DME) has been considered as one of the main routes to produce clean fuel, that is, DME. Thus, efficient catalysts are highly required for selective production of DME. Herein, UiO-66 was used as a precursor for the synthesis of zirconium oxide sulfate embedded carbon (ZrOSO4@C). The synthesis method involves a one-step carbonization of UiO-66 in the presence of sulfuric acid (10 wt %). Material characterizations using X-ray diffraction, X-ray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…The results of this experiment are shown in Figure 2(c). Examination of these results infers that, at a reaction temperature of 190 °C, curves of both PY and DMPY are almost coinciding indicating the presence of Brønsted acid sites as major together with little amount of Lewis acid sites [58,59,61,62] …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this experiment are shown in Figure 2(c). Examination of these results infers that, at a reaction temperature of 190 °C, curves of both PY and DMPY are almost coinciding indicating the presence of Brønsted acid sites as major together with little amount of Lewis acid sites [58,59,61,62] …”
Section: Resultsmentioning
confidence: 96%
“…The acid‐base properties of the bentonite sample calcined at 200 o C,were measured adopting isopropyl alcohol (IPA) dehydration/dehydrogenation method [58–60] and the obtained results are presented in Figure 2(b). Inspection of these results revealed that, at all reaction temperatures, propene was the only product with a selectivity of 100 % reflecting the acidic nature of bentonite sample [59,61,62] . In addition, as the reaction temperature increases, the % conversion of IPA increases to reach 100 % at 200 °C.…”
Section: Resultsmentioning
confidence: 97%
“…Zeolitic imidazolate frameworks (ZIFs), [ 1–11 ] a class of metal organic frameworks, [ 12,13 ] have been applied for several applications such as catalysis, biomedical, [ 14 ] and environmental‐related fields. ZIFs materials offer several advantages including large surface area, tunable pore size, active metal sites, and good thermal and chemical stability due to the strong coordination bonds between the metal centers and linker donating atoms such as ‐N‐.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several approaches were reported to reduce anthropogenic CO 2 concentration in the atmosphere. Applications of metal‐organic frameworks (MOFs), [ 4,3,13,28–34 ] including ZIFs for CO 2 adsorption are promising [ 22,35 ] for lowering the concentration of greenhouse gases in the atmosphere. [ 36–39 ] MOFs [ 40 ] have been applied as catalysts for the chemical fixation and photochemical reduction of CO 2 , [ 41 ] and as adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles exhibit distinct properties such as large surfaces, many active sites, and high adsorption capacities compared to bulk materials. Thus, they have been applied for several applications such as analytical chemistry [17][18][19][20][21][22][23][24][25][26], proteomics [27], sensing/biosensing [28][29][30][31][32][33][34][35], biotechnology [36][37][38][39][40][41][42][43][44][45], nanomedicine [46][47][48][49][50][51][52][53], drug delivery [54][55][56], gene transfer [57][58][59][60], wound healing [61], energy-based applications [62][63][64]…”
Section: Introductionmentioning
confidence: 99%